Exploring Gamer English Usage: Insights from a Narrative Inquiry - Nasution, Hikmal Maulana; Fauzi, Iwan; Emeral; Muliawan, Sunanda Alam; Jami, Sonia Vriska Yulinda (General English Education, 2026)
Games are increasingly recognized as effective tools for supporting language learning, particularly in the development of speaking and pronunciation skills. While previous studies have highlighted the potential of digital games for language learning, fewer have examined informal online gaming experiences from learner narrative perspectives, especially in relation to speaking and pronunciation development. This study explores how a recent high school graduate improved his English proficiency through online gaming, aiming to understand how informal and extramural activities contribute to language development outside the classroom. Using a narrative inquiry approach, data were collected through semi-structured interviews, transcribed, and thematically analyzed to capture the participant personal experiences. The findings reveal that online gaming provided meaningful exposure to English and motivated the participant to communicate more actively with teammates. Through interactions on platforms such as Discord and PlayStation Party, the participant practiced pronunciation, expanded vocabulary, and received immediate feedback from other players. The collaborative and immersive nature of gaming created a low-anxiety environment that increased confidence and willingness to speak. These results demonstrate that language learning can occur beyond formal education and that extramural activities offer rich opportunities for authentic language use.